2021
DOI: 10.1029/2020gc009278
|View full text |Cite
|
Sign up to set email alerts
|

Convective and Tectonic Plate Velocities in a Mixed Heating Mantle

Abstract: Mantle convection and, by association, plate tectonics is driven by the transport of heat from a planetary interior. This heat comes from the internal energy of the mantle and from heat flowing into the base of the mantle from the core. Past investigations of such mixed mode heating have revealed unusual behavior that confounds our intuition based on end‐member cases. In particular, increased internal heating leads to a decrease in convective velocity. We investigate this behavior using a suite of numerical ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…In contrast, an additional argument for the promotion of stagnant lid behaviour independent of rheological arguments may come from the physics of mantle systems heated from below and within. In such systems, high levels of radiogenic heating tend to inhibit convection, and thus stress imparted via internal convective velocities, due to transition in convective planforms from predominantly sheet-like to plume-like Lenardic et al 2021).…”
Section: Evolution Of the Upper Mantle And Crustmentioning
confidence: 99%
“…In contrast, an additional argument for the promotion of stagnant lid behaviour independent of rheological arguments may come from the physics of mantle systems heated from below and within. In such systems, high levels of radiogenic heating tend to inhibit convection, and thus stress imparted via internal convective velocities, due to transition in convective planforms from predominantly sheet-like to plume-like Lenardic et al 2021).…”
Section: Evolution Of the Upper Mantle And Crustmentioning
confidence: 99%
“…As shown, the statistical behavior of the models (the average values) varies with temperature dependence of the viscosity and the internal heating rate. The geotherm plots show that higher values of the internal heating rates diminish the deep mantle layering (e.g., Lenardic et al., 2020; Moore, 2008; Sotin & Labrosse, 1999).…”
Section: Model Resultsmentioning
confidence: 99%
“…Figures 2 and 3 show results from several suites of numerical experiments. The suites follow from the study of Lenardic et al [2021] (full model equations and solution procedures can be found in that reference). Models are formulated in terms of a basal heating Rayleigh number (Ra) and a ratio of the internal to basal heating Rayleigh numbers (H ).…”
Section: Conceptual Arguments and Numerical Experimentsmentioning
confidence: 99%
“…Moore [2008] developed theoretical scaling relationships that predict how thermal outputs should vary with H and Ra for mixed heating convection in an active lid mode. The theory has been extensively tested against numerical convection experiments in both 3-D Cartesian [Lenardic et al, 2021] and 3-D Spherical modeling domains . We can use the theory, calibrated to a spherical geometry in line with Earth mantle dimensions, to test the ability of continuous plate tectonics to account for observational constraints.…”
Section: Quantitative Scaling Analysismentioning
confidence: 99%
See 1 more Smart Citation